Pengaruh Kepemimpinan dan Kompensasi Terhadap Disiplin Kerja Karyawan Pada PT Pegadaian (Persero) CP Malimongan Baru di Makassar - Nuur Alya Muslimah; M Irfan Maulana Bima (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This research aims to determine the influence of leadership and compensation on employee work discipline at PT. Pegadaian (Persero) CP Malimongan Baru in Makassar. This research approach uses a quantitative approach. The sample used was the census method, totaling 62 respondents. And then the data analysis model used is multiple linear regression analysis which was processed using the SPSS Version 23 program. Based on the results of research that has been conducted, it shows that the influence of leadership and compensation has a positive and significant effect on employee work discipline at PT. Pegadaian (Persero) CP Malimongan Baru in Makassar.